Productivity of Inbred Rice (Oryza Sativa L.) as Influenced by the Application of Gibberellic Acid (GA3) - Ronquillo, Shelah; Martin Jr, Artemio (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study aimed to evaluate the effects of varying concentrations and application timing of Gibberellic acid 3 (GA3) on the growth and yield performance of inbred rice (NSIC Rc 222). Grounded in plant physiological theory, the research examined how GA3 influences vegetative and reproductive development under field conditions. A Randomized Complete Block Design (RCBD) was employed with ten treatments, including control groups and varying GA3 concentrations applied at different growth stages. The study was conducted in Magassi, Cabagan, Isabela, using standard agronomic practices and field-based measurements such as plant height, tiller number, panicle length, culm length, grain filling, and yield. Data were analyzed using Analysis of Variance (ANOVA) and Tukey’s Honestly Significant Difference (HSD) test. Results revealed that GA3 significantly increased plant height and culm length, particularly when applied at 25 and 50 days after transplanting. However, no significant improvements were observed in the number of productive tillers, panicle length, number of filled grains, grain yield per plot, or computed yield per hectare. In some cases, higher GA3 concentrations resulted in reduced grain filling and lower yield performance. The findings indicate that GA3 primarily enhances vegetative growth but does not improve reproductive development or overall yield. It is recommended that GA3 application be minimized in inbred rice production under similar conditions, and further studies should explore alternative concentrations, timings, and site-specific factors. This study aligns with Sustainable Development Goals SDG 2 (Zero Hunger), SDG 12 (Responsible Consumption and Production), and SDG 13 (Climate Action) by addressing sustainable rice production and efficient input use. The findings contribute to agricultural sustainability by promoting evidence-based practices that support resource efficiency, climate resilience, and improved farm productivity.